Affecting Factors Of Competitive Advantage: A Conceptual Model Development For Wooden Crafts Industry In Bali, Indonesia - Ni Nyoman Adityarini Abiyoga Vena Swara; Ni Nyoman Kerti Yasa; I Gst Ngurah Jaya Agung Widagda K; Gede Suparna (Jurnal Ekonomi dan Bisnis Jagaditha, 2025)
The purpose of this study is to demonstrate the contribution of SMEs in increasing the attractiveness and value of Balinese tourism. SMEs achieve this by complementing the tourism sector and improving the overall tourism image through the creation of innovative products by Balinese craftsmen, which are strongly embedded in the arts and culture of Tri Hita Karana. The wood industry is the dominant craft sector in Bali, although its production capacity is still relatively modest compared to other industries. The competitive advantage of wood products is determined by several external and internal variables. This study uses a literature review methodology. Data analysis in the literature review includes the preparation and presentation of conclusions obtained from several data sources obtained. The result of this study is a theoretical framework that combines social media strategies and innovation as intermediary elements to reduce the negative impact of external and internal factors on competitive advantage. This study aims to increase knowledge in the field of management strategy, specifically focusing on the competitive advantage of Balinese wooden craft goods. Based on empirical research and interviews with participants in the wood craft business, it is hypothesized that three elements-competitive intensity, entrepreneurial orientation, and technological orientation-have an impact on competitive advantage.